Designing User Interface (UI) And User Experience (UX) of a Sport Space Rental Application using Design Thinking Method - Raissa Maringka; Cherry Lumingkewas (CogITo Smart Journal, 2024)
This study aims to enhance the design and streamline the process of renting sports facilities through the development of a user interface (UI) and user experience (UX) for a sport space rental application. Utilizing the Design Thinking method, the research addresses inefficiencies in the current manual booking process and proposes innovative solutions, including search features, user reviews, availability notifications, and direct booking options. The state of the art in this study is represented by the application of user-centric design principles and iterative prototyping to meet the evolving needs of sports enthusiasts. Usability testing, conducted through detailed task scenarios on the MAZE platform, yielded positive results, with an average completion rate of 80% and insights into areas for improvement. The findings suggest that the proposed UI/UX design significantly enhances the efficiency and user experience of renting sports facilities, providing a more convenient and engaging platform for users.